Upaya Meningkatkan Hasil Belajar Ilmu Pengetahuan Alam (IPA) dengan Metode Pembelajaran Two Stay Two Stray (TSTS) - Syaeful Bachri; Dasmo Dasmo (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Indraprasta PGRI, 2017)
The purpose of this research is to improve the result of studying science using two stays two strays (TSTS) learning method by controlling the students’ ability in the beginning. This research used the experimental method with ANAKOVA analysis. The sample used is the students of class VIII SMP Negeri 242 Jakarta with 60 students’ divided into control and experimental class with each totaling 30 samples. The results of this research are: First, controlling influence the students’ ability, in the beginning, there is difference result of studying science which is significant between the students who study by using two stays two stray and using conventional method (Fhitung = 15,05 > Ftabel = 4,01). Second, controlling influence the students’ ability, in the beginning, the result of study science, the students who study by using stay two stray is better than using conventional model (thitung = 3,892 > ttabel = 1,672).